Pengaruh Lingkungan Kerja Terhadap Produktivitas Pegawai Pada CV Sukses Karya Lestari Kota Gunungsitoli (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2024)
The work environment encompasses everything around employees while they are working, both in physical and non-physical forms, which can influence them in carrying out their tasks and daily work. A conducive work environment provides a sense of security that enables employees to work optimally. The work environment can affect employees' emotions. If an employee enjoys the work environment where they work, they will feel comfortable in their workplace. A conducive work environment will have a positive impact on the company; conversely, if the work environment is less conducive, it will have a negative impact on the company. The problem formulation in this research is to determine whether there is an Influence of the Work Environment on Employee Productivity at CV. Sukses Karya Lestari, Gunungsitoli City. This research uses quantitative research to determine the influence of an independent variable on the dependent variable in a study and the extent of its role with the aim of testing the established hypotheses. The research sample is the entire population size due to the limited number of respondents studied. From the research results, it is known that the levels of validity of variables X and Y meet the applicable standards with the overall results of the questionnaire items declared valid because r calculated > r table (0.334), at a confidence interval of 95% with N = 35. The research instruments for each variable are also declared reliable with r calculated X (0.495) > r table (0.334) and r calculated Y (0.526) > r table (0.334) at a confidence interval of 95% with N = 35. The calculation of the determination correlation shows that there is an influence of variable X (work environment) on variable Y (employee productivity in the production department) by 23.9%, while 76.1% is influenced by other factors not discussed in this study.
Keywords: Work Environment, Employee Productivity.